Modeling Enrollment in and Completion of Vocational Education: The Role of Cognitive and Non-Cognitive Skills by Program Type - Leslie S. Stratton; Nabanita Datta Gupta; David Reimer; Anders Holm (Institute of Labor Economics (IZA), 2017)
This study provides evidence of the importance of cognitive and non-cognitive skills to enrollment in and completion of three types of vocational training (VET): education and health, technical, and business. Math and language exam scores constitute the key measures of cognitive skills; teacher-assigned grades the key measure of non-cognitive skills. The data consist of two nine-year panels of youth completing compulsory education in Denmark. Estimation of completion proceeds separately by gender and VET type, controlling for selection and right censoring. The authors find that all skills are inversely related to VET enrollment, results that are robust to family-specific effects. Estimates for completion vary considerably by program type, demonstrating the methodological importance of distinguishing among different VET courses. While math scores are positively related to certification for all VET tracks, language skills are more important for the nontechnical track, and non-cognitive skills appear important only for the business track.
Keywords: I21; 330; vocational education; enrollment; completion; vocational certification; ability